The health status, social support, and subjective well-being of older individuals: evidence from the Chinese General Social Survey - Zhang, Yuchen; Sun, Longyu (Frontiers in Public Health, 2024)
Objectives This study aims to investigate the impact of health status and social support on the subjective well-being of older individuals. Methods Using data from the China General Social Survey 2017, this research analyzed 5,187 Chinese citizens aged 60 years and older. The predicted effect of each variable on subjective well-being was evaluated through hierarchical regression analysis. The direct and indirect effects of social support and health status on subjective well-being are examined based on a structural equation model. Results The mental health and social support positively impact subjective well-being. Mental health mediates the effect of physical health on subjective well-being, and social support mediates the relationship between physical and mental health and subjective well-being. Conclusion The findings provide strong evidence for the interrelationship mechanisms among the factors influencing subjective well-being. Consequently, improving mental health services and social support systems is advantageous for enhancing the well-being of Chinese seniors.